Differences in Self-Esteem and Self-Confidence Among Adolescents with Acne Vulgaris by Gender - Shally Ayu Chintya; Siti Khomsatin; Luluk Faridatul Mukaromah (Journal of Global Research in Public Health, 2026)
Acne vulgaris is a common inflammatory skin condition among adolescents that can affect psychological aspects, particularly self-esteem and self-confidence, due to changes in physical appearance. This study aims to determine differences in self-esteem and self-confidence among adolescents with acne vulgaris based on gender. This study employed a quantitative design with a cross-sectional approach. The sample consisted of 90 adolescents, including 37 males and 53 females, selected using purposive sampling. Data were analyzed using the Mann–Whitney U test because they were not normally distributed. The results showed no significant difference in self-esteem between male and female adolescents (p = 0.434). However, there was a significant difference in self-confidence (p = 0.009), with female adolescents exhibiting higher levels of self-confidence compared to males. In conclusion, gender does not affect self-esteem but does influence self-confidence among adolescents with acne vulgaris.